Omens and superstitutions of southern India - Thurston, Edgar (Chennai : MJP Publishers, 2022)
Omens, Animal superstitions, The Evil Eye, Snake Worship, Vows, Votive and other offerings, Charms, Human Sacrifice, Magic and Human life, Magic and Magicians, Divination and Fortune-telling, Some Agricultural Ceremonies, Rain-making Ceremonies.
Keywords: Folklore; Superstitions